Content Analysis Of The House Sales Brochure By PT Bela Berlian Mandiri - Muhammad Kadafih Alfajri; Hanifa Nur Fadhilla (International Journal of Economics, Business and Innovation Research, 2024)
This study analyzes the content of the house sales brochure by PT Bela Berlian Mandiri. In an era where digital strategies increasingly dominate marketing, brochures still play an important role in attracting the interest of potential buyers. This research identifies informational cues and creative strategies used in the brochures to capture market attention and boost sales. Through a quantitative approach, by analyzing seven marketing brochures of PT Bela Berlian Mandiri, the study aims to gain a deep understanding of the effectiveness of brochures as a marketing tool. The results show that the use of informative and creative brochures can strengthen relationships with potential buyers and increase interest in the properties offered.